CHARACTERISTICS OF GAS SHALE IN DAKEBO FORMATION, AT WAGHETE AREA - PAPUA PROVINCE - Tobing, Robert Lumban (Buletin Sumber Daya Geologi, 2015)
Dakebo Formation is found in Akimeugah Basin. The formation is interpreted as Pliocene in age and itÂ is sedimented on alluvial fan and flood plain environment, composed by conglomerate, sandstone,Â sandy shale, mudstone and lignite. In megascopic view, samples of rock in this area are blackishÂ gray. Among shale beds there are thin sandstones and limestones layers as well as remains ofbrownish to blackish plants. The organic geochemistry and maceral analyses indicate that samples of rock contain organic material with fair to very good classification as source rocks, and consist ofÂ vitrinite and liptinite macerals. The presence of vitrinite maceral is ârare to majorâ and liptinite is ârare toÂ commonâ. Based on the TOC analysis, abundance of the organic material is about 3.11% to 12.62%Â with type II and type III kerogen. TÂ value is about 401ÂºC to 431ÂºC and Rv is 0.28% to 0.31%Â indicated that organic material is immature. Kerogen type II has prone to produce oil and type III hasÂ prone to produce gas.Â